Duration of a ”Brown-Like” Phenotype of White Adipose Tissue Induced by the β3 Agonist CL-316,243 - Danysz, Wojciech; Jinlai, Kang; Li, Fugang (Drug Research, 2019)
“Browning” i. e. the transformation of white adipose tissue into brown-like adipose tissue could induce efficient burning of excess fat reserves via induction of non-shivering thermogenesis. For example, activation of ß3 adrenergic receptors has been show to induce such changes, however, it is still not clear, how long after termination of such a treatment, beneficial effects might be maintained. To address this question, we treated rats s.c. for 2 weeks with the ß3 agonist CL-316,243 at 1 mg/kg and assessed interscapular brown fat and inguinal white fat pads weight, UCP-1 (a marker for the brown-like fat phenotype) using immunohistochemistry and H&E staining, at different intervals after treatment termination.One 1 day after the treatment cessation there was a decrease of inguinal white fat pad weight and increase of interscapular fat pad. This change vanished at 7 days for inguinal pad and at 14 days for interscapular pad. Histological analysis of interscapular pads showed increased UCP-1 staining and brown-like morphology in H&E staining slices at 1 day, but not other time points. In case of inguinal pad there were brown-like features in H&E slices at 1 day and less after 7 days, but absent at 14 days. UCP-1 staining was only detected 1 day after the treatment.In conclusion, the present results indicate that browning-like changes of white fat may be short lasting after treatment termination and could require maintenance treatment of inductor to achieve desired therapeutic effect. This might be a serious shortcoming of potential therapeutic use.
Keywords: WAT; BAT; browning; UCP-1; H&E